Effectiveness of AI-Based Chatbots as Virtual Tutors in Basic Programming Education - Setiawan, Arif; Irfanuddin, Muhammad Fikri; Adhisa, Ryan Rizki (Universitas Negeri Padang, 2024)
The integration of AI-based chatbots as virtual tutors in basic programming education addresses the challenges posed by the diverse backgrounds of students and the complexity of the course material. This integration aims to provide personalized assistance and explanations tailored to individual student needs and understanding levels. The research methodology employed in this study adopts a Research and Design (RnD) approach, utilizing the 4D development model, which encompasses the stages of Definition, Design, Development, and Deployment. Through this methodology, the study aims to develop and evaluate the effectiveness of the chatbot in enhancing students' learning experiences. The results of the study indicate a significant increase in students' self-learning activities, as evidenced by a score of 79.4% in the